2018
DOI: 10.1080/14733315.2018.1435026
|View full text |Cite
|
Sign up to set email alerts
|

VOC emission rates in newly built and renovated buildings, and the influence of ventilation – a review and meta-analysis

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles VOC emission rates in newly built and renovated buildings, and the influence of ventilationa review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Reducing the volatile compounds in Several studies have focused on the IAQ of newly built buildings and its change over time (Seifert 1992;Wolkoff 1999;Scholz and Santl 1999;Bornehag and Stridh 2000;Rehwagen et al 2003;Raw et al 2004;Järnström et al 2006). These studies indicate that the concentrations of VOCs in the indoor air of newly built buildings are much higher than the guideline values specified by each country, and Holøs et al (2019) indicated that the off-gassing phase would last at least 2 years. However, Tuomainen et al (2001) showed that VOC concentrations in new houses constructed using low-emitting materials could be reduced by ventilating the houses for 1 week, and Noguchi et al (2016) also concluded that operating the ventilation system for 3 months would effectively reduce VOCs in newly constructed buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the volatile compounds in Several studies have focused on the IAQ of newly built buildings and its change over time (Seifert 1992;Wolkoff 1999;Scholz and Santl 1999;Bornehag and Stridh 2000;Rehwagen et al 2003;Raw et al 2004;Järnström et al 2006). These studies indicate that the concentrations of VOCs in the indoor air of newly built buildings are much higher than the guideline values specified by each country, and Holøs et al (2019) indicated that the off-gassing phase would last at least 2 years. However, Tuomainen et al (2001) showed that VOC concentrations in new houses constructed using low-emitting materials could be reduced by ventilating the houses for 1 week, and Noguchi et al (2016) also concluded that operating the ventilation system for 3 months would effectively reduce VOCs in newly constructed buildings.…”
Section: Introductionmentioning
confidence: 99%
“…While our recommendations are focused on combustion-related air pollution, ventilation may also serve to decrease the impact of chemicals in the home (e.g. from cleaning products and off-gassing from carpets and furniture), although a recent review suggests that indoor volatile organic compounds are attenuated more by time than by ventilation [149].…”
Section: Improved Ventilationmentioning
confidence: 99%
“…During non-occupied periods, the levels remained relatively low (<300 µg/m 3 ). This could be because both dwellings are more than five years, and tVOC off-gassing is usually higher in new (<2 years) materials [67]. Monthly tVOC levels and statistical analyses can be found in Supplementary Table S3.…”
Section: Total Volatile Organic Compoundsmentioning
confidence: 99%